Impact of COVID-19 infection on cyclooxygenase-2 gene expression and mast cell count in testicular tissue of azoospermic men: COVID-19 effects on testicular inflammation in azoospermic men - Kalhor, Zahra; Allahvaisi, Azra; Rezaie, Mohammad Jafar; Daneshdust, Rezgar; Nikkhoo, Bahram; Rahmani, Khaled (Cellular and Molecular Biology, 2024)
The COVID-19 pandemic has posed significant threats to human life and health. Numerous studies have shown that men are more vulnerable to this infection, and recent evidence suggests that the presence of angiotensin-converting enzyme 2 (ACE2) receptors in male reproductive tissues may particularly predispose them to viral infection. Therefore, it is crucial to assess the potential impact of COVID-19 infection on male fertility. This study investigates the relationship between COVID-19 and the expression of inflammatory proteins, particularly mast cells and cyclooxygenase-2 (COX-2), in the testicular tissue of azoospermic men undergoing testicular sperm extraction (TESE). The study included 41 TESE candidates who were referred to the Besat Infertility Treatment Center in Kurdistan, Iran. Demographic information, such as age, was recorded for each participant. The subjects were divided into two groups: 20 non-infected and 21 infected with COVID-19. Testicular tissue samples were fixed in formalin and prepared for microscopic examination using toluidine blue staining and immunohistochemistry to assess the distribution and number of mast cells and COX-2 positive cells. Data analysis was performed using SPSS software version 27. The results showed that COX-2 gene expression and the number of mast cells were significantly higher in individuals infected with COVID-19 compared to the non-infected group. This increase in gene expression and mast cell count indicates elevated inflammation in the testicular tissue of COVID-19-infected individuals, which could lead to reduced fertility. This study aligns with previous research highlighting the role of inflammation in testicular tissue damage and decreased fertility.